1980
DOI: 10.1136/pgmj.56.657.526
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypokalaemia with paralysis induced by small doses of liquorice

Abstract: SummaryA patient, who presented with a flaccid quadriplegia due to profound hypokalaemia, is described. Hypokalaemia and myoglobinuria were caused by the ingestion of small amounts of liquorice contained in a laxative preparation. Subsequent controlled administration of small amounts of this preparation induced marked hypokalaemia. This was associated with sodium retention and potassium loss confirming a mineralocorticoid-like action. The sodium retention was associated with suppression of plasma levels of ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A case of flaccid quadriplegia due to profound hypokalemia has been reported to be due to ingestion of small amounts of liquorice contained in a laxative preparation taken in combination with antihypertensive treatment (not specified in the original paper) [32]. The interaction could be due to an additive effect of potassium excretion as both some antihypertensives and liquorice (which possess mineralcorticoid effects) can cause potassium excretion [56,61].…”
Section: Interaction With Antihypertensivesmentioning
confidence: 99%
“…A case of flaccid quadriplegia due to profound hypokalemia has been reported to be due to ingestion of small amounts of liquorice contained in a laxative preparation taken in combination with antihypertensive treatment (not specified in the original paper) [32]. The interaction could be due to an additive effect of potassium excretion as both some antihypertensives and liquorice (which possess mineralcorticoid effects) can cause potassium excretion [56,61].…”
Section: Interaction With Antihypertensivesmentioning
confidence: 99%
“…A 70-year old woman was admitted to hospital with a flaccid quadriplegia which proved to be due to severe hypokalemia [43]. The problem turned out to be the result of relatively small amounts of liquorice (G/ycyrrhiza glabra) taken in combination with antihypertensive treatment.…”
Section: Herb-drug Interactionsmentioning
confidence: 99%
“…An important thing to remem ber is that GIHM may be caused by a very small amount of GL. For example, Cumming et al [25] reported 1 case of weakness following severe hypokalemia caused by the administration of GL in a dose of 94 mg/day for only 11 days.…”
Section: Mechanism O F Gihmmentioning
confidence: 99%